what is the solution set for this quadratic formula: x^2 - 3x = -4

x^2 - 3x = -4 x^2 - 3x + 4 = 0 a = 1, b = -3, c = 4 discriminant = b^2 - 4ac = (-3)^2 - 4(1)(4) = 9 - 16 = -7 < 0 There are no real roots for the equation x^2 - 3x = -4 Two complex roots are x = [3 ± sqrt (-7)]/2 = [3 ± (sqrt 7)i]/2

s

Question

Asked 3/21/2012 2:34:47 PM

Updated 1/27/2015 11:58:54 PM

1 Answer/Comment

Rating

3

x^2 - 3x = -4

x^2 - 3x + 4 = 0

a = 1, b = -3, c = 4

discriminant = b^2 - 4ac = (-3)^2 - 4(1)(4) = 9 - 16 = -7 < 0

There are no real roots for the equation x^2 - 3x = -4

Two complex roots are x = [3 ± sqrt (-7)]/2 = [3 ± (sqrt 7)i]/2

x^2 - 3x + 4 = 0

a = 1, b = -3, c = 4

discriminant = b^2 - 4ac = (-3)^2 - 4(1)(4) = 9 - 16 = -7 < 0

There are no real roots for the equation x^2 - 3x = -4

Two complex roots are x = [3 ± sqrt (-7)]/2 = [3 ± (sqrt 7)i]/2

Added 1/27/2015 11:58:54 PM

This answer has been confirmed as correct and helpful.

solve for v.... 6/v=9/v-1/2

Question

Expert Answered

Updated 9/20/2014 10:57:20 PM

2 Answers/Comments

6/v=9/v-1/2

6/v - 9/v = -1/2

-3/v = -1/2

v = -3/( -1/2)

v= -3 *(-2)

v = 6

6/v - 9/v = -1/2

-3/v = -1/2

v = -3/( -1/2)

v= -3 *(-2)

v = 6

Added 9/20/2014 10:56:18 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [9/20/2014 11:00:45 PM]

multiply... (4x+4)(6x^2 +8x+3) **Weegy:** a.
Factor as:
(x - 3)(x + 1)^3 = 0
zeros are at x = 3 and x = -1
y ' = 4x^3 - 12x - 8
4(x - 2)(x + 1)^2
zeros at x = 2 and x = -1
- - - - - - - - - - - - - - - - - - - -
b.
y " = 12x^2 - 12
y "(2) = 36 which is positive, [ so x = 2 is a minimum point
y "(-1) = 0, an inflection point
- - - - - - - - - - - - - - - - - - - -
c.
f(x) decreases from [-8, 2] and increases from [2, +8]
- - - - - - - - - - - - - - - - - - - -
d.
f(x) is negative for x = [-1, 3] and positive for all other real values ] (More)

Question

Expert Answered

Updated 3/21/2012 11:26:01 AM

3 Answers/Comments

(4x+4)(6x^2 +8x+3) = 24x^3 + 56x^2 + 44x + 12

Added 3/20/2012 10:42:09 AM

This answer has been confirmed as correct and helpful.

Unflagged by andrewpallarca [7/7/2014 7:25:01 PM], Confirmed by andrewpallarca [7/7/2014 7:25:03 PM]

multiply (s+f)(s^2 - sf +f^2)
**Weegy:** f^3 + s^3 is the answer. (s+f)(s^2 - sf +f^2) = f^3 + s^3 (More)

Question

Expert Answered

Asked 3/20/2012 12:48:15 PM

0 Answers/Comments

multiply (r+1/5)(r+1/4)
**Weegy:** r^2 + 9r/20 + 1/20 (More)

Question

Expert Answered

Asked 3/20/2012 1:17:17 PM

0 Answers/Comments

factor completely... 4x^8 - 12x^7 + 24x^6
**Weegy:** 4x^8 - 12x^7 + 24x^6
= 4x^6 (x^2 - 3x + 6) (More)

Question

Expert Answered

Updated 7/11/2014 12:10:08 AM

0 Answers/Comments

31,875,394

questions answered

There are no comments.